Financial Challenge: Are State-Owned Banks on the IDX Overly Dependent on Financial Ratios? - Abdul Rasyid (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study is encouraged by the need to understand the relationship between financial ratios and the performance of state-owned banking companies in Indonesia. In the context of a complex banking industry and dynamic economic development, a deeper understanding of the influence of financial ratios on company performance is essential for making the correct managerial decisions. This research analyzes the influence of financial ratios, namely the Current Ratio, Quick Ratio, and Cash Ratio, and their effect on Return on Assets in state-owned banking companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach is used by utilizing annual financial statement data for the past five years, from 2017 to 2021, and statistical analysis is run with the help of the SPSS program. The analysis process involves a series of statistical tests, such as the Classical Assumption Test, which includes normality, multicollinearity, autocorrelation, and heteroscedasticity tests. Multiple Regression Analysis, Coefficient of Determination Test (R2), and T-Statistical Test were also conducted. The results of hypothesis testing show that Current Ratio has a positive and significant effect on Return on Assets, while Quick Ratio shows a significant negative impact, as well as Cash Ratio on Return on Assets. This study is expected to provide in-depth insights for relevant stakeholders in financial management, strategic planning, and investment decision-making in the state-owned banking sector. Through a quantitative approach with secondary data analysis, this study is expected to significantly contribute to understanding the financial dynamics of state-owned companies in the Indonesian capital market.